The potential of IFN-λ, IL-32γ, IL-6, and IL-22 as safeguards against human viruses: a systematic review and a meta-analysis - Sattar, Areej A.; Qaiser, Ariba; Kausar, Hina; Aqil, Sarah; Mudassar, Rida; Manzoor, Sobia; Ashraf, Javed (Frontiers in Immunology, 2024)
Many studies have investigated the antiviral activity of cytokines, including interleukin-6 (IL-6), interleukin-22 (IL-22), interleukin-32 gamma (IL-32γ), and interferon-lambda (IFN-λ) in diverse populations. This study aims to evaluate the role of these cytokines in inhibition of various human and animal viruses when administered exogenously. A comprehensive meta-analysis and systematic review were conducted on all the relevant studies from three databases. Standard mean differences (SMDs) of overall viral inhibition were used to generate the difference in the antiviral efficacy of these cytokines between control and experimental groups. A total of 4,618 abstracts for IL-6, 3,517 abstracts for IL-22, 2,160 abstracts for IL-32γ, and 1,026 abstracts for IFN-λ were identified, and 7, 4, 8, and 35 studies were included, respectively, for each cytokine. IFN-λ (SMD = 0.9540; 95% CI: 0.69–0.22) and IL-32γ (SMD = 0.459; 95% CI: 0.02–0.90) showed the highest influence followed by IL-6 (SMD = 0.456; CI: −0.04–0.95) and IL-22 (SMD = 0.244; 95% CI: −0.33–0.81). None of the cytokines represented heterogeneity (tau² > 0), but only IFN-λ indicated the funnel plot asymmetry (p = 0.0097). Results also indicated that IFN-λ and IL-32γ are more potent antivirals than IL-6 and IL-22. The collective findings of this study emphasize that exogenously administered pro-inflammatory cytokines, specifically IFN-λ and IL-32, exhibit a significant antiviral activity, thereby underscoring them as potent antiviral agents. Nonetheless, additional research is required to ascertain their clinical utility and potential for integration into combinatorial therapeutic regimens against viral infections.